PARIWISATA DIGITAL: TRANSFORMASI PEMASARAN PARIWISATA INDONESIA MELALUI INSTAGRAM DAN YOUTUBE PEMERINTAH SELAMA MASA PANDEMI COVID-19 - Alfarida Herlina (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
This paper discusses the impact of social restrictions during the COVID-19 pandemic on the tourism sector and the role of the government in efforts to recover from the impacts that occurred through several programs, especially social marketing on social media (owned media). The use of social media is the right choice and a reliable solution as an effort to transform sustainable tourism marketing. This program will not run effectively without a good marketing strategy. The selection and use of promotional content affects the message to be conveyed. Therefore, this study seeks to analyze the content of social media content (Instagram and Youtube) belonging to the Ministry of Tourism and Creative Economy of the Republic of Indonesia and analyze the effectiveness of the promotional content.